Partners vs. Strangers: identification of the Group Membership in the Contribution to Public Goods (2014)
This paper studies the effect of experience, the inter-temporal strategy and the group size as the possible explanations to the highest levels of contribution to equilibrium in a game of public goods -- All these variables together allow capturing the effect of the group membership; keeping in mind that the more information collected about its members' behavior, the greater the levels of contribution -- Therefore, treatment was implemented in which subjects interact in a group with permanent members (partners), and other treatment where the group changes randomly in each round (strangers) -- In addition, crossed treatments were carried out, in which first stage partners or strangers’ status is surprisingly changed in the second stage of the experiment -- Groups of four or five members were considered to analyze the effect of the group size -- Results show that the average contribution is positive and gradually converges to the Nash equilibrium as repetitions increase -- Although there is evidence in favor of the intertemporal strategy, it critically depends on the stability of the group's composition -- Regarding the group size, four-member groups show a higher average contribution